Antimycobacterial Activity and Low Cytotoxicity of Leaf Extracts of Some African Anacardiaceae Tree Species. (13th September 2016) - Kabongo‐Kayoka, Prudence N.; Eloff, Jacobus N.; Obi, Chikwelu L.; McGaw, Lyndy J.
Abstract : Treatment of tuberculosis (TB) is a challenge because of multidrug‐resistant and extremely drug‐resistant strains of Mycobacterium tuberculosis . Plant species contain antimicrobial compounds that may lead to new anti‐TB drugs. Previous screening of some tree species from the Anacardiaceae family revealed the presence of antimicrobial activity, justifying further investigations. Leaf extracts of 15 Anacardiaceae tree species were screened for antimycobacterial activity using a twofold serial microdilution assay against the pathogenic Mycobacterium bovis and multidrug resistant M .  tuberculosis and rapidly growing mycobacteria, Mycobacterium smegmatis, Mycobacterium fortuitum and Mycobacterium aurum . The vaccine strain, M .  bovis and an avirulent strain, H37Ra M .  tuberculosis, were also used. Cytotoxicity was assessed using a colorimetric assay against Vero kidney, human hepatoma and murine macrophage cells. Four out of 15 crude acetone extracts showed significant antimycobacterial activity with minimum inhibitory concentration varying from 50 to 100 µg/mL. Searsia undulata had the highest activity against most mycobacteria, followed by Protorhus longifolia . M .  fortuitum was the strongest predictor of activity against multidrug‐resistant TB (correlation coefficient = 0.65). Bioautography against M .  aurum and M .  fortuitum worked well as indicators of the Rf values of active compounds yielding strong zones of inhibition. The leaf extracts of S .  undulata and P .  longifolia had more than ten different antimycobacterial compounds and had low cytotoxicity with LC50 values above 100 µg/mL. Copyright © 2016 John Wiley & Sons, Ltd.